Physical and Mechanical Properties of Fiber Board from Corn Husk Fiber - Rita Desiasni; Fauzi Widyawati; Yuliana Fitri Sersaningsih; Syamsul Bahtiar; Amirin Kusmiran (JPSE (Journal of Physical Science and Engineering), 2022)
Using agricultural waste materials, namely corn husk fiber (CHF), to reduce agricultural waste and recycle corn husk waste into sustainable engineering materials is relatively significant due to the decreasing number of woods. This study aims to analyze the effect of the volume fraction of CHF with polyester (PE) on the physical and mechanical strength of fiberboard composites with variations in volume fraction of 25  percent fiber : 75 percent PE, 50 percent fiber : 50 percent PE, and 75 percent fiber : 25 percent PE. Composites are made by the hand layup method. Fibers were pretreated by immersing 5 percent NaOH for 2 hours. The results of testing the physical properties of the highest density composite board at a volume fraction of 25 percent fiber : 75 percent PE of 0.85 g/cm³ and the lowest moisture absorption value was at 0.49 percent. The results of the mechanical board test in the form of the modulus of elasticity (MOE) test got the highest test value at the fiber volume fraction 25 percent fiber : 75 percent PE, which was 1179.2 MPa as well as the highest modulus of rupture (MOR) test value was found in the volume fraction 25 percent fiber: 75 percent PE that is equal to 9.4 MPa. Based on this result research, the average strength of the mechanical properties increases with the increase in the number of matrices. That indicates a reasonably good bond between the fiber and the matrix. The results of the water content test also increased as the density value increased.DOI: 10.17977/um024v7i22022p134